Artificial Intelligence in Autism Spectrum Disorder: Technological Innovations to Enhance Quality of Life: A Holistic Review of Current and Future Applications - Rêgo, Ph.D., Amália Cinthia Meneses do; Araújo-Filho, Irami (International Journal of Innovative Research in Medical Science, 2024)
Integrating Artificial Intelligence (AI) into healthcare, specifically for managing Autism Spectrum Disorder (ASD), offers transformative potential to enhance diagnostic accuracy, personalize treatment, and improve patient outcomes. This review explores the application of various AI programs in ASD management, discussing their functionalities, ethical considerations, implementation challenges, and the need for comprehensive regulatory frameworks. Critical AI applications such as AI-driven diagnostic imaging, predictive analytics, assisted therapy robots, remote monitoring, treatment personalization, decision support systems, and therapeutic chatbots are examined. Each technology is analyzed for its ability to improve the quality of life for individuals with ASD by offering more personalized, efficient, and effective care and support. Ethical issues, particularly concerning data bias and privacy, are highlighted as significant challenges that need addressing to maximize AI's benefits while minimizing risks. Practical hurdles like integration with existing healthcare systems, the need for scalable solutions across diverse geographic and socio-economic contexts, and the high costs associated with AI development are also discussed. Furthermore, the review underscores the necessity for robust regulatory policies that ensure patient safety, protect data privacy, and maintain high ethical standards in AI deployment. The paper concludes that while AI presents substantial opportunities for advancing ASD management, achieving these benefits requires a concerted effort from technologists, clinicians, ethicists, and policymakers to develop AI tools that are not only innovative but also ethical, equitable, and universally beneficial.